Immunochromatography for the diagnosis of Mycoplasma pneumoniae infection: A systematic review and meta-analysis. - Seo Hee Yoon (PLoS ONE, 2020)
The aim of this study was to evaluate the diagnostic performance of immunochromatographic tests (ICTs) for the detection of Mycoplasma pneumoniae. Medline/Pubmed, Embase, the Cochrane Library, and ISI Web of Science were searched through June 12, 2019 for relevant studies that used ICTs for the detection of M. pneumoniae infection with polymerase chain reaction (PCR) or microbial culturing as reference standards. Pooled diagnostic accuracy with 95% confidence interval (CI) was calculated using a bivariate random effects model. We also constructed summary receiver operating characteristic curves and calculated the area under the curve (AUC). Statistical heterogeneity was evaluated by χ2 test or Cochrane's Q test. Thirteen studies including 2,235 samples were included in the meta-analysis. The pooled sensitivity and specificity for diagnosing M. pneumoniae infection were 0.70 (95% CI: 0.59-0.79) and 0.92 (95% CI: 0.87-0.95), respectively. The positive likelihood ratio (LR) was 8.94 (95% CI: 4.90-14.80), negative LR 0.33 (95% CI: 0.22-0.46), diagnostic odds ratio 29.20 (95% CI: 10.70-64.20), and AUC 0.904. In subgroup analysis, ICTs demonstrated similar pooled sensitivities and specificities in populations of children only and mixed populations (children + adults). Specimens obtained from oropharyngeal swabs exhibited a higher sensitivity and specificity than those of nasopharyngeal swab. Moreover, pooled estimates of sensitivity and accuracy for studies using PCR as a reference standard were higher than those using culture. The pooled sensitivity and specificity of Ribotest Mycoplasma®, the commercial kit most commonly used in the included studies, were 0.66 and 0.89, respectively. Overall, ICT is a rapid user-friendly method for diagnosing M. pneumoniae infection with moderate sensitivity, high specificity, and high accuracy. This suggests that ICT may be useful in the diagnostic workup of M. pneumoniae infection; however, additional studies are needed for evaluating the potential impact of ICT in clinical practice.